Automatic surveillance in transportation hubs: No longer just about catching the bad guy. Issue 24 (30th December 2015) - Denman, Simon; Kleinschmidt, Tristan; Ryan, David; Barnes, Paul; Sridharan, Sridha; Fookes, Clinton
Highlights: Surveillance and video analytics systems are typically only used for security. We explore how emerging video analytics can support security and operations needs. A conceptual framework combining security and operations is proposed. An analysis of the proposed framework as applied to an airport is presented. We show how many technologies have dual applications, and the benefits this brings. Abstract: As critical infrastructure such as transportation hubs continue to grow in complexity, greater importance is placed on monitoring these facilities to ensure their secure and efficient operation. In order to achieve these goals, technology continues to evolve in response to the needs of various infrastructure. To date, however, the focus of technology for surveillance has been primarily concerned with security, and little attention has been placed on assisting operations and monitoring performance in real-time. Consequently, solutions have emerged to provide real-time measurements of queues and crowding in spaces, but have been installed as system add-ons (rather than making better use of existing infrastructure), resulting in expensive infrastructure outlay for the owner/operator, and an overload of surveillance systems which in itself creates further complexity. Given many critical infrastructure already have camera networks installed, it is much more desirable to better utilise these networks to address operational monitoring as well as security needs. Recently, a growing number of approaches have been proposed to monitor operational aspects such as pedestrian throughput, crowd size and dwell times. In this paper, we explore how these techniques relate to and complement the more commonly seen security analytics, and demonstrate the value that can be added by operational analytics by demonstrating their performance on airport surveillance data. We explore how multiple analytics and systems can be combined to better leverage the large amount of data that is available, and we discuss the applicability and resulting benefits of the proposed framework for the ongoing operation of airports and airport networks.